Coping Strategies to Survive Online Learning Difficulties: Qualitative Survey Study of Bataknese and Javanese Students - Daulay, Nurussakinah; Fransiska, Widia (Gadjah Mada Journal of Psychology (GamaJoP), 2024)
It is apparent that students’ perceptions of the online learning experience during the pandemic led to the development of coping abilities to deal with stress. This research aims to explore coping mechanisms that Batak and Javanese students in Medan City used to minimise stress related to online learning difficulties during the COVID 19 pandemic. A total of 671 students participated in the study by completing a self-reported survey online. This research is qualitative research with a thematic analysis approach. The findings were categorized into two main themes: 1) online learning difficulties (consisting of 3 subthemes: technical problems, task overload, emerging negative emotions); 2) overcoming online learning difficulties (consisting of 3 subthemes: patience, prayer, and parental support). This research implies that the coping strategies students use can help them survive adversity during the COVID-19 pandemic.